The Influence of Leadership Behavior, Quality of Work Life and Work Motivation on the Performance of Lecturers - Rusydi Ananda; Farida Isnaini; Muhammad Rifai (Journal La Edusci, 2026)
This study examines the effects of leadership behavior, quality of work life, and work motivation on lecturer performance at IAIN Takengon. Using a quantitative ex post facto research design, data were collected from 97 lecturers through structured questionnaires and analyzed using descriptive statistics, correlation analysis, and path analysis. The results indicate that leadership behavior and quality of work life have significant direct effects on both work motivation and lecturer performance. Work motivation emerges as the strongest predictor of lecturer performance and also functions as a significant mediating variable in the relationships between leadership behavior and performance, as well as between quality of work life and performance. The simultaneous analysis shows that leadership behavior, quality of work life, and work motivation jointly explain a substantial proportion of the variance in lecturer performance. These findings highlight the importance of effective leadership practices, supportive working conditions, and sustained motivation in enhancing lecturer performance in higher education institutions. The study contributes to the existing literature by providing empirical evidence of an integrated model that explains lecturer performance through the interaction of organizational and psychological factors within the context of Islamic higher education